CD8+ T Cell Exhaustion in Cancer - Dolina, Joseph S.; Van Braeckel-Budimir, Natalija; Thomas, Graham D.; Salek-Ardakani, Shahram (Frontiers in Immunology, 2021)
A paradigm shift in the understanding of the exhausted CD8+ T cell (Tex) lineage is underway. Originally thought to be a uniform population that progressively loses effector function in response to persistent antigen, single-cell analysis has now revealed that CD8+ Tex is composed of multiple interconnected subpopulations. The heterogeneity within the CD8+ Tex lineage comprises PD1-expressing immune checkpoint blockade permissive and refractory subsets termed stem-like precursors and terminally differentiated cells, respectively. These populations occupy distinct peripheral and intratumoral niches and are characterized by transcriptional processes that govern the transition between cell states. This review presents key findings in the field to construct an updated view of the spatial, transcriptional, and functional heterogeneity of anti-tumoral CD8+ Tex. These emerging insights broadly call for (re-)focusing cancer immunotherapies to center on the driver mechanism(s) underlying the CD8+ Tex developmental continuum aimed at stabilizing functional subsets.